Superconvergence of finite element method for parabolic problem - Do Y. Kwak; Sungyun Lee; Qian Li (International Journal of Mathematics and Mathematical Sciences)
We study superconvergence of a semi-discrete finite element scheme for parabolic problem. Our new scheme is based on introducing different approximation of initial condition. First, we give a superconvergence of uh−Rhu, then use a postprocessing to improve the accuracy to higher order.